Increasing the dose of television advertising in a national antismoking media campaign: results from a randomised field trial. Issue 1 (16th December 2015) - McAfee, Tim; Davis, Kevin C; Shafer, Paul; Patel, Deesha; Alexander, Robert; Bunnell, Rebecca
Abstract : Background: While antismoking media campaigns have demonstrated effectiveness, less is known about the country-level effects of increased media dosing. The 2012 US Tips From Former Smokers (Tips) campaign generated approximately 1.6 million quit attempts overall; however, the specific dose–response from the campaign was only assessed by self-report. Objective: Assess the impact of higher ad exposure during the 2013 Tips campaign on quit-related behaviours and intentions, campaign awareness, communication about campaign, and disease knowledge. Methods: A 3-month national media buy was supplemented within 67 (of 190) randomly selected local media markets. Higher-dose markets received media buys 3 times that of standard-dose markets. We compared outcomes of interest using data collected via web-based surveys from nationally representative, address-based probability samples of 5733 cigarette smokers and 2843 non-smokers. Results: In higher-dose markets, 87.2% of smokers and 83.9% of non-smokers recalled television campaign exposure versus 75.0% of smokers and 73.9% of non-smokers in standard-dose markets. Among smokers overall, the relative quit attempt rate was 11% higher in higher-dose markets (38.8% vs 34.9%; p<0.04). The higher-dose increase was larger in African-Americans (50.9% vs 31.8%; p<0.01). Smokers in higher-dose markets without a mental health condition, with a chronic health condition, or with only some college education made quit attempts at a higher rate than those in standard-dose markets. Non-smokers in higher-dose markets were more likely to talk with family or friends about smoking dangers (43.1% vs 35.7%; p<0.01) and had greater knowledge of smoking-related diseases. Conclusions: The US 2013 Tips antismoking media campaign compared standard and higher doses by randomisation of local media markets. Results demonstrate the effectiveness of a higher dose for engaging non-smokers and further increasing quit attempts among smokers, especially African-Americans.